2016
DOI: 10.13004/kjnt.2016.12.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Preventable and Potentially Preventable Traumatic Death Rates in Neurosurgery Department: A Single Center Experience

Abstract: ObjectivePreventable and potentially preventable traumatic death rates is a method to evaluate the preventability of the traumatic deaths in emergency medical department. To evaluate the preventability of the traumatic deaths in patients who were admitted to neurosurgery department, we performed this study.MethodsA retrospective review identified 52 patients who admitted to neurosurgery department with severe traumatic brain injuries between 2013 and 2014. Based on radiologic and clinical state at emergency ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Additionally, the death rate in men was significantly higher compared to women. Many findings support our data; some authors reported an increased level of mortality with age and gender; higher level in men with TBI was found [ 12 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the death rate in men was significantly higher compared to women. Many findings support our data; some authors reported an increased level of mortality with age and gender; higher level in men with TBI was found [ 12 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…traumatic brain injury (TBI), and exsanguination are recognised as the most frequent time-sensitive pathologies and account for approximately 70% of all trauma-related deaths within the acute phase after impact [6,7]. Rapid exsanguination has also been identified as the most common cause of preventable death after trauma, even during the prehospital phase of care [7][8][9], and this is frequently due to a delay in treatment (52.9% of cases in one study [10]). These epidemiological data underline the important burden that trauma continues to exercise on healthcare systems, society and individuals.…”
Section: Causes Mechanisms and Timing Of Deaths In Traumamentioning
confidence: 99%
“…When in-hospital time for diagnostic procedures is added-for example, the time to access either whole body or selected computed tomography (CT)-the injured patient rarely receives interventional/surgical care before 2-3 h after the initial impact and this at best. Some of this delay is related to the fragmentation of pre-and intra-hospital care, including time-consuming and anachronistic methods and errors in communication [8,25,26].…”
Section: Efficient Management Of Severe Trauma: a Time-sensitive Approachmentioning
confidence: 99%
“…Furthermore, patients with a contralateral intracranial hemorrhage after a decompressive craniectomy have a worse prognosis than those with uneventful recoveries. 4 20 22 23) Identifying risk factors for postoperative contralateral hemorrhage (PCH) could help establish a treatment strategy and predict the prognosis of TBI patients. Therefore, the objective of this study was to identify risk factors for PCH in patients who underwent a unilateral craniectomy or craniotomy due to TBI.…”
Section: Introductionmentioning
confidence: 99%